Urdu Hamdiyya Qasida Nigari in Karachi: کراچی میں اُردو حمدیہ قصیدہ نگاری - Saqib, Abbas Ali Shah; Bhandara, Asif Afzal; Hanif, Fozia (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
Hamdiah qasidah describes the commendation and praise of Allah Almighty. Qasidah is consist of four parts (Tashbeeb, Gurez, Madah and Duaa).The title of this article is (کراچی میں اُردو حمدیہ قصیدہ نگاری).This article describes the different aspects of Hamdiah Qasidah and Toheed. This poetic form, rooted in Islamic tradition, services as a poignant expression of love, admiration, spiritual devotion and explains the Natural system. Its enduring presence in Urdu literature underscores its significance as a bridge between the realms and religious veneration. Renowed poets like Asar Zuberi, Sahir Lakhnavi, Ghulam Ali Wafa, Raffee۔u۔deen Raz and Shaaer Ali Shaaer have contributed significantly to development Urdu Hamdiah Qasidah in Karachi.